Special vest for people with verbal communication difficulties / Imran Ahmad Nainy, Amirul Rashidi Abdul Rahman and Azeem-Zaki Mohd Mardzukhi - Ahmad Nainy, Imran; Abdul Rahman, Amirul Rashidi; Mohd Mardzukhi, Azeem-Zaki (2015)
This project is called special vest invented for people with verbal communication difficulties. This vest can help a handicapped with the communication disabilities to get through their daily life such as asking for the nearest bus station or asking for helps and many more. Furthermore, this circuit has a 2 mode which are Record mode and Playback mode. The record mode will allow you to record a message up to 60 seconds. This is because we used ISD2560 which for information stored data allow us to record up to 60 seconds. However we had split the 60 seconds to 4 so we have 4 message and 15 second each message. Since the people with verbal communication difficulties cannot record the message by themselves, they had to ask for the person nearest to them to record the message. The playback mode will playback the message stored. The audio was recorded using an electric condense microphone. It was then playback through a speaker.